A Sociological Reading Of Health Security - Ibrir,Leila; Taib, Amel (University of Eloued جامعة الوادي, 2025)
الملخص: تتضمن هذه الورقة البحثية موضوع الأمن الصحي بإعتباره من أهم المواضيع في الدراسات الأمنية الحديثة، وكذلك من المواضيع المطروحة على الأجندة السياسية الدولية نظرا لأهمية الصحة ودورها في منظومة الأمن الإنساني والتنمية المجتمعية الشاملة، لذلك جاءت هذه الورقة للتطرق إلى الأمن الصحي من الناحية الإجتماعية والإقتصادية والسياسية، بالإضافة إلى تأثيره الجوهري على الإستقرار الإجتماعي، ولذلك أصبحت الدول تعمل على تحقيق الأمن الصحي الذي يواجه تهديدات عدة يمكن أن تحدث حالة من اللاأمن الصحي الذي يؤثر سلبا على الإستقرار الإجتماعي، وكذا على السياسات المنتهجة على الصعيد الدولي والمحلي.Abstract: This research paper includes the topic of health security as one of the most important topics in modern security studies, as well as among the topics on the international political agenda due to the importance of health and its role in the system of human security and comprehensive community development. We have touched on health security from a social, economic and political point of view, in addition to its fundamental impact on social stability. Therefore, countries are working to achieve health security, which faces several threats that could create a state of health security that negatively affects social stability, as well as on the policies pursued at the international and local levels .
Keywords: health security; health care; health spending; health culture; الامن الصحي; الرعاية الصحية; الإنفاق الصحي; الثقافة الصحية